HUBUNGAN PROFITABILITAS DENGAN AUDIT DELAY PADA PERUSAHAAN MANUFAKTUR SEKTOR ANEKA INDUSTRI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Annafi Indra Tama (JRAK: Journal of Accounting Research and Computerized Accounting, 2015)
This research is to know whether there are a relationship profitability with audit delay at miscellaneous industry listed in Indonesia Stock Exchange (IDX) or not. Test of analysis condition performed with test of estimated normality error Y on X with Liliefors test which resulted in Lcal(0,1516) < L(0,1517) it’s showed that data was normally distributed.Hypothesis test started with looking for simple regression which in this study yielded in Ŷ= 96,11 - table 47,0603X. Test regression linierity resulted in Fcal (4,35) > F (4,17) it’s showed a linear regression model. Calculation from Pearson’s product moment correlation coefficient revealed that rtable = -0,3559 meant there was a negative correlation between profitability and audit delay. Calculation of correlation coefisient significance resulted t cal (-2,086) > t table xy (1,697) meant that correlation between profitability and audit delay is significantwhile test of determination coeficient revealed 12,67% profitability affect audit delay. Therefore, the study concluded there was a negative significant correlation between profitabilityandaudit delay at miscellaneous industry listed in Indonesia Stock Exchange (IDX)